2021
DOI: 10.1021/acsabm.1c00214
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Carboxymethyl Cellulose/Agar-Based Functional Films Hybridized with Alizarin and Grapefruit Seed Extract

Abstract: Carboxymethyl cellulose/agar-based functional halochromic films were fabricated by adding alizarin and grapefruit seed extract (GSE). The fillers were evenly dispersed in the polymer matrix to form compatible composite films. The addition of alizarin has improved the film's mechanical strength (20%) and water resistance (40%) with potent antioxidant and excellent color indicating properties. In contrast, GSE has imparted strong antibacterial and antioxidant activities to the film. Also, the addition of alizari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…The barberry pigment was reddish/crimson under acidic conditions and yellowish under alkaline conditions, while the saffron pigment was reddish/pink under acidic conditions and greenish/yellow under alkaline conditions. Similar pH-induced color changes have been reported for anthocyanins derived from other plant sources (alizarin and grapefruit seed) that were incorporated into carboxymethyl cellulose/agar films [ 13 ]. These results highlight the pH sensitivity of the anthocyanin-loaded biopolymer films, which may be useful for monitoring changes in the quality or freshness of some foods.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The barberry pigment was reddish/crimson under acidic conditions and yellowish under alkaline conditions, while the saffron pigment was reddish/pink under acidic conditions and greenish/yellow under alkaline conditions. Similar pH-induced color changes have been reported for anthocyanins derived from other plant sources (alizarin and grapefruit seed) that were incorporated into carboxymethyl cellulose/agar films [ 13 ]. These results highlight the pH sensitivity of the anthocyanin-loaded biopolymer films, which may be useful for monitoring changes in the quality or freshness of some foods.…”
Section: Resultssupporting
confidence: 68%
“…However, the antimicrobial effect between the two pigments was not statistically significant. Other researchers have also shown that the addition of pigments containing phenolic compounds inhibits the growth of microorganisms [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the high carbon content, resulting in a high heat tolerance (Niazi et al, 2015, Kiwalczyk et al, 2021. Similar results were found by Roy et al (2021b), who found that when GSE and alizarin is added to the chitosan lm could effectively increase the thermal stability of the lm. Similar results were obtained by Niazi et al (2015).…”
Section: Differential Scanning Calorimetry (Dsc) Analysissupporting
confidence: 87%
“…It has recently been shown that polysaccharide-protein mixtures are useful for making biodegradable active packaging films [ 10 , 11 , 12 , 13 , 14 , 15 ]. For this purpose, chitosan and gelatin are ideal choices for producing binary blends of biopolymer films.…”
Section: Introductionmentioning
confidence: 99%